Un enemigo natural de Unaspis citri (Homoptera, Diaspididae) para Cuba - Hernandez, D.=700 1 Rodriguez, J.L.
(Es, En)
Ilus., 16 ref.
Keywords: UNASPIS; HOMOPTERA; DIASPIDIDAE; ENEMIGOS NATURALES; APHITIS; HYMENOPTERA; RELACIONES HUESPED PARASITO; CUBA; UNASPIS CITRI; CIENCIA Y TECNICA EN LA AGRICULTURA: CITRICOS Y OTROS FRUTALES